The University as Engine of Development? - McCowan, Tristan (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2018)
The idea of the ‘developmental university’ was popularised on the African continent in the post- independence period, but has recently returned to view on account of the positioning of the university in the newly agreed United Nations Sustainable Development Goals. The developmental model is characterised by service to society, application of knowledge, non-academic benefit and prioritising the most marginalised. Yet to what extent are these goals and characteristics coherent and viable given the nature of the university as institution? While the developmental model per seis limited to a few experiences, the implications of these questions are much broader, given the public service mission held by many if not most higher education institutions around the world. After outlining its historical emergence, this article presents a conceptual exploration of the model, highlighting three major limitations, in spite of its highly positive intentions: its positioning of the university as an ‘adaptable factory’, its encroachment on a distinctive space for the university in relation to society, and its particular and contested conception of development.